Does the antenatal detection of fetal growth restriction (FGR) have a prognostic value for mortality and short-term morbidity for very preterm infants? Results from the MOSAIC cohort. (16th February 2016) - El Ayoubi, Mayass; Jarreau, Pierre-Henri; Van Reempts, Patrick; Cuttini, Marina; Kaminski, Monique; Zeitlin, Jennifer; ,
Abstract: Objective : We investigated the impact of antenatal diagnosis of fetal growth restriction (FGR) on the risks of mortality and morbidity for very preterm infants given actual birthweight percentiles. Methods : Data on 4608 live born infants 24–31 weeks of gestational age (GA) in 10 European regions in 2003 were used to compare in-hospital mortality, bronchopulmonary dysplasia (BPD) and severe neurological morbidity by birthweight percentiles and antenatal diagnosis of FGR. Other covariates were GA, sex, multiplicity, maternal complications, antenatal corticosteroids, birth in a level III center and region. Results : Sixteen percent ( n  = 728) of all infants and 72%, 30% and 6%, respectively, of those with birthweight percentiles <10th, 10th–24th and ≥25th had an antenatal diagnosis of FGR. After adjustment for clinical factors, antenatal diagnosis of FGR was not associated with mortality for infants with a birthweight ≥10th percentile (OR [95% CI]: 0.9 [0.5–1.9] and 1.0 [0.6–1.8] for birthweights between the 10th–24th percentile and ≥25th percentile, respectively), but infants with a birthweight <10th percentile had higher mortality (OR [95% CI]: 2.4 [1.0–5.8]). No association was observed at any birthweight percentile with BPD or severe neurological morbidity. Conclusion : Antenatal diagnosis of FGR did not influence risks of mortality or morbidity when birthweight was ≥10th percentile; however, mortality risk was higher in antenatally detected infants with birthweight below the <10th percentile.